Psychometric Properties of the German Version of the Health Regulatory Focus Scale - Schmalbach, Bjarne; Spina, Roy; Steffens-Guerra, Ileana; Franke, Gabriele H.; Kliem, Sören; Michaelides, Michalis P.; Hinz, Andreas; Zenger, Markus (Frontiers in Psychology, 2017)
The Health Regulatory Focus Scale (HRFS) is a short scale which measures an individual’s prevention and promotion focus in a health-specific context. The main objective of this study was to examine the psychometric properties of the newly translated German version of the HRFS. Reliability and item characteristics were found to be satisfactory. Validity of both subscales towards other psychological constructs including behavioral approach and avoidance, core self-evaluations, optimism, pessimism, neuroticism, as well as several measures of physical and mental health was shown. In addition, invariance of the measure across age and gender groups was shown. Exploratory as well as confirmatory factor analyses clearly indicated a two-factorial structure with a moderate correlation between the two latent constructs. Differences in health promotion and prevention focus between socio-demographic groups are discussed. The HRFS is found to be a valid and reliable instrument for the assessment of regulatory focus in health-related environments.